War and peace: exploring microbial defence systems as a source of new antimicrobial therapies - Dyson, Paul J.; Banat, Ibrahim M.; Quinn, Gerry A. (Frontiers in Pharmacology, 2025)
The WHO has compiled a list of pathogens that urgently require new antibiotics in response to the rising reports of antibiotic resistance and a diminished supply of new antibiotics. At the top of this list is fluoroquinolone-resistant Salmonella typhi, fluoroquinolone-resistant Shigella spp. and vancomycin-resistant Enterococcus faecium. Although these problems have been covered in great detail by other contemporary reviews, there are still some fundamental gaps in the translation of current knowledge of the infectious process and the molecular ecology of antibiotic production into a sustainable protocol for the treatment of pathogenic diseases. Therefore, in this narrative review we briefly discuss newly approved antimicrobial drugs (since 2014) that could help to alleviate the burden of multiresistant pathogens listed on the WHO priority list. Being conscious that such treatments may eventually run the risk of future cycles of resistance, we also discuss how new understandings in the molecular ecology of antibiotic production and the disease process can be harnessed to create a more sustainable solution for the treatment of pathogenic diseases.